Mitigation of ion-induced desorption for accelerator components by surface treatment and annealing. (May 2023) - Velthaus, V.; Trautmann, C.; Bender, M.
Abstract: Ion-induced desorption is a serious limitation for beam intensity and life time in heavy ion accelerator facilities. To investigate how gas desorption is affected by surface conditions and bulk materials, oxygen-free copper, tungsten and aluminum samples were irradiated with 4.8 MeV/u Ca and Au ions. The surfaces were pretreated by various combinations of milling, lapping, polishing and etching, while the bulk is conditioned by thermal annealing. For all tested samples desorption yields of H2, H2 O, CO and CO2 are presented. Diamond milling and polishing reduce ion-induced desorption to some extent, but most pronounced effects were achieved by ex-situ thermal annealing at 400 °C for about 4 h under ultra-high vacuum conditions. The decreased desorption persists for at least 9 months of storage in atmosphere. This is a strong indication that for the mitigation of desorption stimulated by high energy ion exposure, not only the surface properties have to be optimized, but also the treatment of the bulk material plays an important role. Storage of annealed samples in argon is favorable compared to storage in atmosphere. Highlights: Reduced ion-induced desorption by ex-situ annealing at 400 °C in UHV environment. Low desorption after annealing persists for 9 mouth of atmosphere storage. For heavy ion-induced desorption bulk properties are as important as the surface. Scaling of desorption yield with ion energy loss is validated for different charge states.